Radiographic evaluation of factors affecting bearing dislocation in the domed lateral Oxford unicompartmental knee replacement. - Gulati, A; Weston-Simons, S; Evans, D; Jenkins, C; Gray, H; Dodd, C; Pandit, H; Murray, D (Elsevier, 2014)
BACKGROUND: The rate of bearing dislocation with the domed lateral Oxford Unicompartmental Knee Replacement (OUKR) in different series varies from 1% to 6% suggesting that dislocation is influenced by surgical technique. The aim of this study was to identify surgical factors associated with dislocation. METHODS: Aligned post-operative antero-posterior knee radiographs of seven knees that had dislocated and 87 control knees were compared. Component alignment and position and the alignment of the knee were assessed. All bearing dislocations occurred medially over the tibial wall. RESULTS: Knees that dislocated tended to be overcorrected: Compared with those that did not dislocate, they were in 2° less valgus (p=0.019) and the tibial components were positioned 2mm more proximal (p<0.01). Although the relative position of the centre of the femoral component and the tibial component was the same (p=0.8), in the dislocating group the gap between the edge of the femoral component and the top of the wall in flexion was 3mm greater (p=0.019) suggesting that the components were internally rotated. CONCLUSIONS: To minimise the risk of dislocation it is recommended that the knee should not be overstuffed. This is best achieved by selecting the bearing thickness that just tightens the ligaments in full extension, and re-cutting the tibia if necessary. In addition to minimise the gap between the femoral and tibial components through which the bearing dislocates, the femoral component should be implanted in neutral rotation and should not be internally rotated. LEVEL OF EVIDENCE: Level IV.